Mexican Community of Historians of Education. Towards an historiographical account of the years 2002-2012 - Aguirre Lora, María Esther; Márquez Carrillo, Jesús (Historia y Memoria de la Educación, 2016)
Every ten years the Mexican Council of Education Research organizes the gathering of information for the «state of knowledge» in seventeen different areas of study. The aim of this activity is to assess the «state of knowledge » in order to discover and to analyze the main tendencies of the decade. Having been directly involved in the gathering of the last «state of knowledge» in relation to the sub-area of History and Historiography of Education, the purpose of this article is to give an account, in general lines, of the processes we followed to collect the information, as well as the global tendencies in the last decade (2002-2012). Given its general nature, the article does not focus on so much on particularities, but rather deals with the central historiographic production of recent years